Egy mezőgazdasági értékesítő szövetkezet stratégiája - Kis, Mária (Jelenkori Társadalmi és Gazdasági Folyamatok, 2008)
In Hungary, the role of collection farms, wich have numerous forms in increasing due to agricultural policy inspiring fusions. Producer Organisations have to be emphasized among collective farms because under the control of European Union’s vegetable and fruit market, subsidy is paid through them. In all fruit an vegetable growing regions of Hungary Growing and Trading Organizations have come into existents, so the geographical cover is nearly complete. There are 58 Producer Organizations currently in Hungary, In 2007 the turnover of product issue in the sector was HUF 179 billion, The fruit and vegetable growing organisations and groups turnover was HUF 35 billion. Their total turnover has been stagnating at about 15% of the total product issue in the sector. Mórakert Cooperatives’s turnover runs to 15-20% of Growing ar.d Trading Organisation’s totai turnover. In my thesis deal with Mórakert Fruit and Vegetable Producer Organization, which is the biggest one in Hungary, its products can be found on the shelves of most domestic supermarket chains.